Analysis of TMJ vibration sounds before and after use of two types of occlusal splints - Mazzeto,Marcelo Oliveira (2009)
Temporomandibular joint (TMJ) sounds are important and common physical signs of temporomandibular disorders (TMD). The aim of this study was to evaluate the influence of the effect of the use of occlusal bite splints (stabilizing and repositioning) on the sounds produced in the TMJ, by means of the electrovibratography (EVG). Thirty-one patients with TMD from the Dental School of Ribeirão Preto, University of São Paulo, Brazil were selected for this study. Group 1 (n=23) wore stabilizing bite splints and Group 2 (n=8) used anterior repositioning splints. Before and after treatment with occlusal splints both groups were analyzed using the SonoPAK Q/S recording system (BioResearch System, Inc.). The treatments with stabilizing bite splints were satisfactory, since they reduced the total amount of the sound energies (p<0.05), but the use of anterior repositioning splints for no more than 4 weeks produced significantly better results (p<0.01). The total amount of vibration energy involved in the vibrating movements of the TMJ showed significant improvement using anterior repositioning splints.